2016
DOI: 10.15344/2456-3498/2016/104
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections Incidence, their Predictors and Causative Organisms in a Teaching Hospital

Abstract: Purposes: Nosocomial infections (NCIs) are infections that generally occur 48 hours after hospitalization. Surgical site infections (SSIs) are the major contributor to patient morbidity, health care costs and death. The rational for this study was to assess the frequency of NCIs in surgical wards and investigate possible predictors for SSIs. Methods: It was an observational and prospective study for the purpose of providing structured opportunities for Hospital administration and health professionals in counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…This finding is contrary to those in studies that revealed more gram-positive bacteria such as Staphylococcus aureus and coagulase-negative staphylococci. 2,25 However, other authors reported findings similar to ours, with more common gram-negative bacteria isolated from the infected abdominal wounds in Al-Ahsa, 11 Saudi Arabia 2 and Tanzania. 5 We also found that most of the pathogens were multiresistant to the commonly prescribed prophylactic anti- biotics.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is contrary to those in studies that revealed more gram-positive bacteria such as Staphylococcus aureus and coagulase-negative staphylococci. 2,25 However, other authors reported findings similar to ours, with more common gram-negative bacteria isolated from the infected abdominal wounds in Al-Ahsa, 11 Saudi Arabia 2 and Tanzania. 5 We also found that most of the pathogens were multiresistant to the commonly prescribed prophylactic anti- biotics.…”
Section: Discussionsupporting
confidence: 78%
“…This finding is in keeping with previous reports in the literature. 5,11 Longer operative time reflects the complexity of the surgery. It would also increase the wound susceptibility to infection by increasing the exposure to potential contamination and decreasing the tissue concentration of antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first such study carried out in the Provincial Hospital of Taza concerning the incidence of SSIs. The SSIs incidence rate, found in this study (6.3%), corroborates with those reported in other studies carried out in Brazil (6.4%) [10], Turkey (4.09%) [11], India (5%) [12], Pakistan (7.3%) [13], and Algeria (5.4%) [14]; while it is lower than that obtained in many other countries: Ethiopia (13%) [15], Egypt (17.6%) [16], Saudi Arabia (11.4%) [17], Nigeria (27.6%) [18] and Tanzania (26%) [19].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of SSI in our centre is lower than in studies done in Pakistan where it was found to be 33.68%. 14 It is still slightly higher than those reported in studies done in Saudi Arabia, 12% 15 and 10.50%. 16 In our study, the rate of SSI was more in adult groups and this result was obtained as more patients admitted and operated on were in adult age groups.…”
Section: Discussionmentioning
confidence: 56%